Selective recognition of DNA parallel G-quadruplexes by 3, 8a-disubstituted indolizinones. (1st January 2021) - Zhang, Jing-Tao; Wang, Li-Xia; Yang, Feng-Min; Yang, Luo; Liu, Yan; Tang, Ya-Lin
Graphical abstract: Abstract: Owing to its potential biological relevance, DNA G-quadruplex has been considered as a prospective anti-cancer target. Some known G-quadruplex-interactive N -containing compounds with low cytotoxicity have become prospective anticancer drugs. Here we reported a new type of N -containing alkaloids 3, 8a-disubstituted indolizinones, and investigated their substituent effects at 3- and 8a-positions in targeting to DNA c-myc G-quadruplex. And then we used 3-naphtyl-8a-(pyridin-2-yl) substrate I8 as an example, and investigated its ability in targeting to DNA parallel G-quadruplexes in vitro.